Come On In: Virtual Reality Beyond the Headset (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
In this paper I consider embodiment, spectatorship, and virtuality as they relate to aesthetic experience and how they can be understood through the interactive installation, Come On In (2020) by dancer, choreographer, and director Faye Driscoll. I argue that virtual reality need not include the use of VR technologies such as headsets, but rather that it is a mode of experience that blurs the boundary between fact and fiction through what Vittorio Gallese calls “embodied simulation.” In Driscoll’s installation, the visitor’s body is used to channel and enact the performance as they are seated or reclined while listening to a kind of guided meditation through headphones. The reclined body then, does not have to be viewed as passive, but rather as facilitating an embodied experience, a claim that is supported by Jacques Rancière’s theory of the emancipated spectator. Further, I look at vulnerability as a condition of cognition (made literal in the reclined body) through David Bates’s historical analysis of the evolution of artificial intelligence, linking the plasticity of cognition with the conception of embodied simulation and immersive experience, to point to the liberatory potential of art.
Keywords: Spectatorship; Embodied simulation; Neuroplasticity; Virtual Reality; Interactive Art